Leaving no stone unturned in light of the COVID-19 faecal-oral hypothesis? A water, sanitation and hygiene (WASH) perspective targeting low-income countries (2020)
The human coronavirus disease (COVID-19) is now a global pandemic. Social distancing, hand hygiene and the use of personal protective equipment dominate the current fight against COVID-19. In developing countries, the need for clean water provision, sanitation and hygiene have only received limited attention. The current perspective examines the latest evidence, on the occurrence, persistence and faecal-oral transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the etiological agent for COVID-19. Evidence shows that SARS-CoV-2 proliferate in the human gastrointestinal system, and is shed via faeces. SARS-CoV-2 can survive and remain viable for up to 6 to 9 days on surfaces. Recent wastewater-based epidemiological studies from several countries also detected SARS-CoV-2 RNA in raw wastewaters. Shell disorder analysis show that SARS-CoV-2 has a rigid outer shell conferring resilience, and a low shell disorder conferring moderate potential for faecal-oral transmission. Taken together, these findings point to potential faecal-oral transmission of SARS-CoV-2, which may partly explain its rapid transmission. Three potential mechanisms may account for SARS-CoV-2 faecal-oral transmission: (1) untreated contaminated drinking water, (2) raw and poorly cooked marine and aquatic foods from contaminated sources, and also raw wastewater-based irrigation (e.g., salads) and aquaculture, and (3) vector-mediated transmission from faecal sources to foods, particularly those from open markets and street vending. SARSCoV-2 faecal-oral transmission could be particularly high in developing countries due to several risk factors, including; (1) poor drinking water, wastewater and sanitation infrastructure, (2) poor hygiene and food handling practices, (3) unhygienic and rudimentary funeral practices, including home burials close to drinking water sources, and (4) poor social and health care systems with low capacity to cope with disease outbreaks. Hence, clean drinking water provision, proper sanitation, food safety and hygiene could be critical in the current fight against COVID-19. Future research directions on COVID-19 faecal-oral transmission are highlighted.